SYSTEMS AND METHODS FOR SHAPE OPTIMIZATION OF STRUCTURES USING PHYSICS INFORMED NEURAL NETWORKS - ZHANG, Zhizhou; WANG, Bingnan; LIN, Chungwei (2025)
A method for training a shape optimization neural network to produce an optimized point cloud defining desired shapes of materials with given properties is provided. The method comprises collecting a subject point cloud including points identified by their initial coordinates and material properties and jointly training a first neural network to iteratively modify a shape boundary by changing coordinates of a set of points in the subject point cloud to maximize an objective function and a second neural network to solve for physical fields by satisfying partial differential equations imposed by physics of the different materials of the subject point cloud having a shape produced by the changed coordinates output by the first neural network. The method also comprises outputting optimized coordinates of the set of points in the subject point cloud, produced by the trained first neural network. L'invention concerne un procédé d'entraînement d'un réseau de neurones d'optimisation de forme pour produire un nuage de points optimisé définissant des formes souhaitées de matériaux ayant des propriétés données. Le procédé comprend la collecte d'un nuage de points sujet comprenant des points identifiés par leurs coordonnées initiales et de propriétés de matériau, et l'entraînement conjoint d'un premier réseau de neurones, destiné à modifier de manière itérative une limite de forme en modifiant les coordonnées d'un ensemble de points du nuage de points sujet pour maximiser une fonction objectif, et d'un second réseau de neurones, destiné à trouver une solution pour des champs physiques en satisfaisant des équations différentielles partielles imposées par la physique des différents matériaux du nuage de points sujet ayant une forme produite par les coordonnées modifiées fournies en sortie par le premier réseau de neurones. Le procédé comprend également la fourniture en sortie de coordonnées optimisées de l'ensemble de points du nuage de points sujet, produites par le premier réseau de neurones entraîné.